PERSEPSI KEY-PERSONS TERHADAP PROSPEK PENDEKATAN CO-MANAGEMENT DALAM PENGELOLAAN SUMBERDAYA IKAN DEMERSAL DI KABUPATEN REMBANG - Sofyan Eko Putra (Universitas Ahmad Dahlan, 2013)
Fishing particularly for demersal fish resources is a business that plays a role in increasing the welfare of coastal communities in the Rembang District Therefore, efforts are needed to manage a sustainable demersal fish resources. This study Co-Management approach with institutional analysis that recommended by ICLARM (Pomeroy and William, 1994 in Susilowati, 1999), which is used to prospect co-management approach and determine the management form of sustainable demersal fish resources in Rembang District.Co-Management Analysis covers physical attributes, community, institutional, actors, and the attributes of demand and supply